(untitled) (The International Journal for Scientific Research, 2026)
This study aims to examine the effect of digital leadership on enhancing organizational agility through the mediating role of knowledge sharing, focusing on Iraqi service companies in Baghdad. In the context of the Fourth Digital Revolution, companies face increasing challenges that necessitate adopting innovative digital strategies to enhance their flexibility and adaptability to rapid changes in the economic and technological environment. Digital leadership emerges as a pivotal factor in guiding organizations towards excellence. It stimulates knowledge exchange and fosters internal collaboration, enhancing organizational agility capabilities such as rapid response and continuous innovation. The study employed a mixed-method approach, combining quantitative and qualitative data, and collected information from 207 employees and managers of prominent Iraqi service companies. Advanced statistical tools such as factor analysis and structural equation modelling were used to measure causal relationships between variables. The results showed a statistically significant positive effect of digital leadership on organizational agility, with a strong mediating role of knowledge sharing in enhancing this effect. The study recommends developing training programs to strengthen digital competencies and cultivate a culture of knowledge sharing to increase the competitiveness of Iraqi institutions in a changing digital environment.